A DURAÇÃO (IR)RAZOÁVEL DO PROCESSO DE RECONHECIMENTO DO STATUS DE REFUGIADO NO BRASIL E A PRECARIZAÇÃO DA VIDA NO LIMBO - Costa, Manuela Coutinho (2020)
The crisis of forced human displacement has reached alarming levels. Year after year, the number of asylum applications grows exponentially globally and nationally. The Brazilian system, when confronted with the migratory reality, proves to be insufficien